Nano-scale control of the ionomer distribution by molecular masking of the Pt surface in PEMFCs. Issue 26 (1st May 2020) - Doo, Gisu; Yuk, Seongmin; Lee, Ji Hye; Choi, Sungyu; Lee, Dong-Hyun; Lee, Dong Wook; Hyun, Jonghyun; Kwon, Sung Hyun; Lee, Seung Geol; Kim, Hee-Tak
Abstract : A new strategy for controlling the ionomer distribution in the catalyst layer of a polymer electrolyte membrane fuel cell, the molecular masking of Pt catalyst particles, is presented to achieve efficient three phase boundaries for the ORR. Abstract : Ionomer films even only a few nanometers thick in the catalyst layer of a polymer electrolyte membrane fuel cell are detrimental to the power performance at low Pt loadings due to their large oxygen transport resistance. Therefore, removing the ionomer films on the Pt surface for oxygen transport while preserving them on the carbon surface for proton transport can be an ideal ionomer distribution. Herein, we achieve ionomer-lean Pt surfaces by masking the Pt nanoparticles of the Pt/C catalyst with an alkanethiol. Due to the weakening of the ionomer/Pt interaction by the molecular mask, a low population of ionomers on the Pt surface is achieved while preserving the fast proton transport in the catalyst layer. The alkanethiol is then electrochemically removed from the catalyst layer, recovering the catalytic activity of the Pt. Electrochemical analyses showed a reduced oxygen transport resistance through the ionomer film and a consequent enhancement of the power performance. This molecular masking strategy marks the beginning of the nano-scale control of ionomer distribution in the development of advanced fuel cells.